SYSTEMATIC LITERATURE REVIEW: BAHAN AJAR MATEMATIKA BERBASIS MULTIMEDIA INTERAKTIF MENGGUNAKAN POWERPOINT DI SMA - Subarkah, Muhamad Rizki; Wardono, Wardono; Susilo, Bambang Eko; Agoestanto, Arief; Sugiman, Sugiman (Universitas Bhinneka PGRI, 2025)
21st-century teaching materials have provided innovations for implementing teaching materials in schools, especially high schools. If students want a new look or color in learning, then interactive multimedia teaching materials can be used for high school. Development to become a teaching material product must go through a validity process by experts and development methods. The aim of this research is only to focus on determining the level of validity and research methods used in its development. The method used is a Systematic Literature Review (SLR). Therefore, a review or review of articles was carried out from the Google Scholar database. The data analysis guide used to select articles was PRISMA. Articles taken from 2020 to 2024. The results of the research accept that use of interactive multimedia-based mathematics teaching materials using PowerPoint can be an alternative learning in several high schools with a good level of validity according to the use of teaching materials, as well as research methods that are widely used in development research, namely (RD).